Arabic Learning Styles at State Islamic Universities in the Society Era 5.0 - Susiawati, Wati (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
This article explained several student learning styles in welcoming the Society Era 5.0. The samples are students from Department of Arabic Language Education, Syarif Hidayatullah State Islamic University of Jakarta and Maulana Malik Ibrahim State Islamic University of Malang. The method used to collect data is direct observation and interviews with teachers and students. The researchers' questionnaires were distributed to students in the fifth semester of the 2020/2021 academic year via the online questionnaire through random sampling. The results showed many students' learning styles at both universities. It was noted that online learning was common, especially during the pandemic 3 years ago. Many applications support the learning process. Student learning styles in both universities relied heavily on rounding, google classroom, WhatsApp Group, and YouTube. Zoom took first place with 96.4% of respondents's answers. Students also need material assistance in the form of videos, ppt and others. It was recorded that 25% of lecturers in the Arabic Language Education Department of the State Islamic University of Jakarta used their YouTube channels as educational means.